The Mediating Marketing Capabilities between Entrepreneurial Orientation, Digital Literacy, and SME Performance - Dewi Lestari; Roni Adi; Karlina Karlina (Penerbit Goodwood, 2026)
Purpose: SMEs in Batam City still face challenges in maintaining performance due to limited resources, marketing, and digital adoption. This study aims to examine how entrepreneurial orientation and digital literacy affect SME performance, with marketing capability serving as a mediating factor. Methodology/approach: Using a causal research design, data were collected from 165 SME owners in Batam through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The findings reveal that entrepreneurial orientation and digital literacy significantly enhance marketing capability, which, in turn, positively influences SME performance. Furthermore, marketing capability mediates the relationship between entrepreneurial orientation and performance, as well as between digital literacy and performance. These results highlight that SMEs need to strengthen their entrepreneurial orientation and digital literacy to enhance marketing capability and achieve sustainable performance. Conclusions: This study concludes that entrepreneurial orientation and digital literacy play a significant role in enhancing marketing capabilities, which, in turn, positively contributes to the performance of SMEs in Batam City. Limitations: This study used cross-sectional data and focused only on SMEs in Batam City, which may limit the generalizability of the results. Reliance on self-reported questionnaires may also have introduced response bias. Contributions: This study demonstrates that entrepreneurial orientation and digital literacy enhance SME performance through marketing capability and offers valuable insights for researchers, practitioners, and policymakers.